Glycine Attenuates Citrobacter rodentium‐Induced Colitis by Regulating ATF6‐Mediated Endoplasmic Reticulum Stress in Mice. Issue 15 (18th June 2021) - Zhang, Yunchang; Jiang, Da; Jin, Yuhang; Jia, Hai; Yang, Ying; Kim, In Ho; Dai, Zhaolai; Zhang, Jinhua; Ren, Fazheng; Wu, Zhenlong
Abstract : Scope: Inflammatory bowel disease (IBD) is an inflammatory gastrointestinal disorder in which endoplasmic reticulum (ER) stress and dysbiosis of the intestinal microbiota are implicated. Glycine supplementation is reported to reduce inflammatory responses in experimental colitis. However, the underlying mechanisms responsible for the beneficial effects remain unclear. Methods and Results: Female C57BL/6 mice are orally administered with glycine (3.5 or 5.2 g kg ‐1 body weight) for 14 continuous days. On day 8 post‐glycine supplementation, the mice are orally inoculated with 2 × 10 9 CFU Citrobacter rodentium ( C. rodentium ). The results show that glycine alleviates C. rodentium ‐induced body weight loss, increased disease activity index and spleen weight, colon length shortening, and colonic hyperplasia. Glycine suppresses the activation and infiltration of inflammatory cells, and secretion of pro‐inflammatory cytokines in the colon tissues. The apoptosis of colon epithelial cells is also abrogated by glycine, which is associated with the inactivation of activating transcription factor 6α (ATF6α)‐C/EBP homologous protein (CHOP) signaling. In addition, glycine administration increases α diversity, restores β diversity, and abolishes the reduction in Lactobacillus, Bifidobacterium, Alistipes, Turicibacter, and Alloprevotella in the colon. Conclusions: Glycine supplementation is a nutritional strategy that may ameliorate C. rodentium ‐induced colitis by regulating ATF6α‐CHOP‐mediated ER stress and enhancing the abundance of Lactobacillus . Abstract : C. rodentium ‐induced colitis is associated with overactivated ER stress. This deleterious effect can be attenuated by glycine through suppressing the ATF6α‐CHOP signaling, which also provided inhibitory effect in inflammatory responses. Supplementation with glycine is a nutritional strategy to alleviate C. rodentium ‐induced inflammatory colon injury in mice.